A MULTI-HIERARCHY GREY RELATIONAL ANALYSIS MODEL FOR NATURAL GAS PIPELINE OPERATION SCHEMES COMPREHENSIVE EVALUATION - Li, Changjun; Jia, Wenlong; Liu, Enbin; Wu, Xia (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
In the condition of satisfying process requirement, determining the optimum operation schemes of natural gas pipeline network is essential to improve the overall efficiency of network operation. According to the operation parameters of natural gas network, the multi-hierarchy comprehensive evaluation index system is illustrated, and the weights of each index are determined with an improved Analytic Hierarchy Process (AHP). This paper presents a multi-hierarchy grey relational analysis (GRA) method which is suitable for evaluating the multi-hierarchy index system with combining the AHP and grey relational analysis. Ultimately, the industrial application shows that multi hierarchy grey relational analysis is effective to evaluate the nature gas pipeline network operation schemes.